ANALISIS PENGELOLAAN KEUANGAN MASJID FATIMAH AT-TUWAIJIRY BEKASI - Eko Susanto; Zul Fadhli Sultani; Fatma Yeni (Universitas Muhammadiyah Prof Dr Hamka, 2021)
The mosque is a place of worship for the Muslim community. Apart from being a place to pray, mosques are also often used as a place to hold religious activities and other social activities such as TPA, breaking fast together, qurban, management meetings, and taklim majlis. Because of the many positive and religious activities that can be held in a mosque, this can be a trigger for the enthusiasm of the mosque congregation, the society or donors to support activities carried out by setting aside some of their assets by providing assistance in the form of money, food. and other forms. Every mosque congregation, the general public or donors who have submitted the assistance that has been distributed, of course, wants what has been submitted to the mosque management to be allocated to things that are useful and in accordance with what they have been entrusted with. Therefore, all parties with an interest in the accountability report for the management of mosque funds expect that they will receive a report whether directly announced every Friday or indirectly, such as a list of receipts and expenditures of funds that is displayed on the mosque wall. The management and financial reporting carried out in each mosque of course have their own differences or characteristics. For example, what happened to one of the mosques in Yogyakarta where the cash owned by the mosque in question always had a zero balance. This is considered very good because any funds that flow to the mosque are always distributed to things that bring benefits to the surrounding community, such as providing boxed rice every Friday and other activities. This study intends to examine how the form of financial management and reporting is carried out by the Fatimah At-Tuwaijiry mosque in Bekasi so that the transparency of its financial reports can be a means of accountability in managing finances mandated by the congregation, the society or donors. The research method used in this study is a qualitative descriptive method, which aims to analyze and provide an overview of the financial reporting and management of the Fatimah At-Tuwaijiry Mosque Bekasi. Data collection techniques were carried out in the form of interviews, observations, and documentation. The results of the study indicate that financial management has been carried out well, this can be seen from the many activities carried out such as holding iftar activities, distributing basic necessities. Keywords: Management, Reporting, Mosque Finance